Quantifying the attitudes of Turkish young generation toward online advertising - Özen, Üstün; Dael, Fares Abdulhafidh (Penerbit Universiti Kebangsaan Malaysia, 2021)
Online advertising is a growing business. Owing to the advances in Internet technology, the nature and types of advertisements (hereinafter, “ads”) have changed. Many companies use different types of advertising to reach their customers. This paper shows how Internet users perceive online advertising. The findings are meant to help companies and institutions develop effective ads that appeal to consumers. Moreover, the study proposes an extended model for the main variables that affect customers’ attitudes toward online advertising. The four variables are credibility, entertainment, informativeness, and irritation. The study was conducted on a sample of Turkish university students. The data were collected via a survey that was administered to participants, and 602 valid responses were used for data analysis. The data were analyzed using SPSS and SmartPLS 3 software. Results revealed that the four hypotheses were supported. Specifically, most users find that the listed types of ads disturb them. Online advertising was negatively perceived by study participants. Through the outcome of this study, the governmental sectors can monitor advertisements, ensure the welfare of users, legislate laws according to what meets the government’s needs and policies. In addition, the study will help companies and institutions to increase the opportunities to accept their advertisements by consumers.